The impact of talent management on human resources efficiency - Altanchimeg Zanabazar; Solongo Natsagdorj; Sarantuya Jigjiddorj (Journal of Social Studies (JSS), 2023)
The belief that talented people create prosperous organizations contributed to the accomplishment of talent management concepts into reality. Highly capable professionals or talented employees who systematically nurtured the best skills typically demonstrate high performance and serve as one of the key success factors for the organizations. Organizations face challenges attracting and maintaining talented employees more than assets. Researches demonstrate that one of the major challenges an organization experience is the aspect of talent management. The objective of the present study is to examine how talent management functions impact the efficiency of human resources. We conducted a sample survey in the metropolitan branch company of the major shareholding company. SPSS 23.0 and Smart PLS 3.0 are used in data analysis and we conducted several tests like reliability tests, correlation analyses, and structural equation models (SEM) to produce the results. The survey results showed that the practice of talent management improves the efficiency of human resources. Moreover, it proved that proper forecasting of talent management needs that foresee opportunity career development and nurture the work culture which would support the mission and vision of the organization makes it possible to increase the efficiency of the human resources.